DEVELOPMENT OF SCIENTIFIC OUTLOOK IN PRESCHOOL CHILDREN THROUGH CENTERS - Saparniyazova Aygul Kutlimuratovna. (Scholar Express Journal, 2022)
This article provides information on the development of scientific outlook in preschool children through centers, its importance, types of centers, and similar information
Keywords: Reading center; wriring center; socially